Nutritional Value of Fermented Palm Oil Fronds as a Basis for Complete Feed for Ruminants - Astuti, T.; Santoso, U.; Amir, Y. (Pakistan Journal of Nutrition, 2017)
Objective: This study aimed to evaluate the nutritional value of a complete feed based on palm oil fronds fermented with microorganisms derived from rumen contents. Methodology: This study used a completely randomized design. The five feed treatment groups with 3 replicates were used. One group was complete feed containing 30% field grass+10% fermented palm oil frond+60% concentrate (R1), the other groups were 20% field grass+20% fermented palm oil frond+60% concentrate (R2), 10% field grass+30% fermented palm oil frond+60% concentrate (R3), 0% field grass+40% fermented palm oil frond+60% concentrate (R4) and 20% field grass+20% palm oil frond+60% concentrate (R5). Results: The experimental results show that the feed treatments significantly affected the contents of dry matter, organic matter, acid detergent fiber, hemicellulose and the digestibility of the dry matter (p0.05). The treatments significantly (p0.05) in Kacang goats. Conclusion: It was concluded that palm oil fronds could be used as forage for Kacang goats.